Micronutrient (provitamin A and iron/zinc) retention in biofortified crops - Bechoff, A.; Taleon, Victor; Carvalho, Lucia M. J.; Carvalho, José L. V.; Boy, Erick (African Journal of Food, Agriculture, Nutrition and Development, 2017)
For biofortification to be successful, biofortified crops must demonstrate sufficient levels of retention of micronutrients after typical processing, storage, and cooking practices. Expected levels of retention at the breeding stage were verified experimentally. It was proven that the variety of biofortified crop, processing method, and micronutrient influence the level of retention. Provitamin A is best retained when the crops are boiled/steamed in water. Processing methods that are harsher on the food matrix (i.e. drying, frying, roasting) result in higher losses of provitamin A carotenoids. Degradation also occurs during the storage of dried products (e.g. from sweet potato, maize, cassava) at ambient temperature, and a short shelf life is a constraint that should be considered when foods are biofortified for provitamin A. Iron and zinc retention were high for common beans (Phaseolus vulgaris) and cowpeas (Vigna unguiculata), indicating that iron and zinc were mostly preserved during cooking (with/without soaking in water).